Findings from the first phase of developing a receptive vocabulary test for the Irish language. (August 2020) - O'Toole, Ciara; Ní Shíthigh, Darina; Molamphy, Aisling; Walsh, Eibhlin
Aims and objectives: The aim of this study was to develop and pilot a test of receptive vocabulary for bilingual Irish-English-speaking children, based on a model from Welsh. Design/Methodology/Approach: 310 typically developing children aged five, six and seven years took part. The children were all attending Irish-medium education in Irish-dominant Gaeltacht regions and in immersion education schools outside of these regions. Data and Analysis: Participants were identified as being from either bilingual Irish- and English-speaking homes or English-dominant homes. A mixed-factorial analysis of variance found a significant main effect of age and language background, but no interaction. Post hoc comparisons revealed that those from Bilingual-speaking homes had significantly higher Irish receptive vocabulary scores than those from English-dominant homes. Linear regression models showed that the receptive vocabulary scores of children in immersion schools grew by an average of 21 words per year between the ages of five and seven, compared to almost 12 words per year in Gaeltacht schools. Findings/Conclusions: The findings demonstrate the advantages of immersion education and the need for vocabulary enrichment of children in the Gaeltacht . However, the complexities of developing assessments for first language speakers of a minority language that is in conflict with a second language variety of that language and the majority English language are also highlighted. Significance/Implications: The implications of this study are that immersion schooling is advantageous to the Irish vocabulary of children, but that children from Gaeltacht schools may require vocabulary enrichment that is sufficiently complex to address their needs. Limitations: Limitations to this study include the uneven number of children from each language background/school location and incomplete background details from the children, such as socio-economic status and language use amongst peers.